IMPROVEMENT OF CORPORATE GOVERNANCE OF COMPANIES IN THE FINANCIAL-ECONOMIC CRISIS - Нусинов, Владимир (Socio-economic relations in the digital society, 2019)
A feature of the activities of Ukrainian companies in this period is that when studying the course of the crisis and when assessing the degree of its severity, its infl uence on the change in results obtained by majority owners becomes the dominant one. Therefore, in our opinion, the severity of the financial and economic crisis of the company should be diagnosed on the basis of changes in the main indicators characterizing the interests of this group of stakeholders. We believe that in the case of diagnosing the fi nancial and economic crisis of the company (especially the average and severe degree of its severity), it is advisable to change the system of its corporate governance. At the same time, it is necessary to involve creditors in its bodies, which will allow them to be involved in the process of restoring the company’s solvency. Inclusion of creditors in the composition of the members of the supervisory board will ensure sufficient number of them to solve key tasks. But at the same time, their involvement in corporate governance has both positive and negative sides. Th is is due to the fact that the time for adaptation of new members of the supervisory board to enter the course of aff airs increases. On the other hand, in this case, it becomes possible to involve more people in the work of committees, which will increase the eff ectiveness of their activities.
Keywords: crisis; economic crisis; financial crisis; bankruptcy; probability of bankruptcy of the company; marginal amount of current liabilities of the company; corporate governance; supervisory board; credit committee; effectiveness of the supervisory board